The role of denture as periodontal splint: Peranan gigi tiruan sebagai splin periodontal - Arni Irawaty Djais; Adhawanty; Eri Hendra Jubhari,; Alfrida Pasangallo; Nurmasyta (Makassar Dental Journal, 2021)
Periodontal disease causes damage to the structure of periodontal tissue characterized by the presence of tooth mobility. Splint is one of the therapies to support the healing of periodontal tissue that aims to provide stability so that occlusal pressure can be evenly distributed to other teeth. The design of dentures that can act as splint is important to maintain the stability of the teeth that mobile while restoring the chewing function. Some designs of denture that can be used as periodontal splint, namely external removable permanent splint and internal fixed permanent splint.